Association between lifestyle and COVID-19 vaccination: A national cross-sectional study - Miao, Yudong; Zhang, Wanliang; Li, Yi; Wu, Jian; Xu, Dongyang; Gu, Jianqin; Wang, Meiyun; Wei, Wei; Ye, Beizhu; Miao, Chengyuan; Tarimo, Clifford Silver; Dong, Wenyong (Frontiers in Public Health, 2022)
Objective To assess lifestyles, COVID-19 vaccination coverage rates, and the relationships between lifestyles and COVID-19 vaccination among Chinese population. Methods We collected data on sociodemographics, perception of the COVID-19 pandemic, lifestyles, and self-reported COVID-19 vaccination via an online survey in China. The chi-square goodness-of-fit test was used to monitor sample saturation throughout the formal online survey. The binary logistic regression analyses were conducted to examine the association between COVID-19 vaccination rate and lifestyle score. We assigned values to 12 lifestyles ranging from positive to negative, with positive lifestyles receiving a higher score and negative lifestyles receiving a lower score, ranging from 1 to 5. For each participant, the total lifestyle scored from 12 to 56. Restricted cubic spline (RCS) was used to visualize the trends and correlations between lifestyle score and COVID-19 vaccination coverage. Propensity score matching (PSM) was used to explore the association between specific lifestyles and COVID-19 vaccination. Results A total of 29,925 participants (51.4% females) responded. The lifestyle score of the sample was 44.60 ± 6.13 (scoring range: 12–56). COVID-19 vaccination rate was found to be 89.4% (89.1–89.8%). Female participants reported a higher vaccination rate than male participants (91.5 vs. 87.1%). Compared to Q1, COVID-19 vaccination coverage rates increased with lifestyle total scores [ORQ2 = 1.901 (1.718–2.103), P < 0.001; ORQ3 = 2.373 (2.099–2.684), P < 0.001; and ORQ4 = 3.765 (3.209–4.417), P < 0.001]. After applying PSM, it was determined that all the 12 specific healthy lifestyles analyzed, including maintaining a healthy body weight, a healthy diet, regular physical exercises, adequate sleep, regular physical examination, and others, were found to be positive factors for COVID-19 vaccination. Conclusion The majority of mainland Chinese lived a healthy lifestyle throughout the COVID-19 pandemic, and the rate of COVID-19 vaccination was high. Specific healthy lifestyles contributed to COVID-19 vaccination coverage rates significantly. According to the study's findings, global efforts to achieve herd immunity should be prioritized by continually promoting healthy lifestyles and improving public perception of COVID-19 vaccines.